Osmotically induced membrane tension modulates membrane permeabilization by class L amphipathic helical peptides: nucleation model of defect formation. - Polozov, I V (2001)
The mechanism of action of lytic peptides on membranes is widely studied and is important in view of potential medical applications. Previously (I. V. Polozov, A. I. Polozova, E. M. Tytler, G. M. Anantharamaiah, J. P. Segrest, G. A. Woolley, and R. M., Biochemistry, 36:9237--9245) we analyzed the mechanism of membrane permeabilization by 18L, the archetype lytic peptide featuring the class L amphipathic alpha-helix, according to the classification of Segrest et al. (J. P. Segrest, G. de Loof, J. G. Dohlman, C. G. Brouillette, and G. M. Anantharamaiah, 1990, Proteins, 8:103--117). We concluded that the 18L peptide destabilizes membranes, leading to a transient formation of large defects that result in contents leakage and, in the presence of bilayer-bilayer contact, could lead to vesicle fusion. Here we report that this defect formation is strongly enhanced by the membrane tension induced by osmotic swelling of vesicles. Even below standard leakage-inducing peptide/lipid ratios, membrane resistance to osmotic tension drops from hundreds to tens of milliosmoles. The actual decrease is dependent on the peptide/lipid ratio and on the type of lipid. We propose that under membrane tension a peptidic pore serves as a nucleation site for the transient formation of a lipidic pore. The tension is released upon pore expansion with inclusion of more peptides and lipids into the pore lining. This tension modulation of leakage was observed for other class L peptides (mastoparan, K18L) and thus may be of general applicability for the action of membrane active lytic peptides.